(untitled) (Interdisciplinary Studies Journal, 2024)
This article aims to analyze the perception regarding the discipline of sociology and its prospects for training in the area of ​​social sciences based on research on the profile of sociology students at the Federal Institute of Bahia, in the city of Juazeiro. This is a localized study in order to contribute data to identify the impact of the accelerated precariousness and devaluation of training and teaching in human sciences, in Brazil, in general. To this end, a survey was carried out with students of the subject in the institution’s high school through a questionnaire administered via Google Forms. After this, the research data, the socioeconomic profile of the students at the Federal Institute of Bahia de Juazeiro and their understandings regarding the role of social sciences for the citizenship and critical formation of subjects were analyzed from the perspective of the context of Brazilian capitalism. As a result, it was identified that young people, despite liking and finding the subject of sociology important in high school education, do not see training in the area as a possibility for the future, which in a way corroborates the little space it occupies. in the secondary school curriculum.